An investigation of lime addition to fuel as a countermeasure to bed agglomeration for the combustion of non-woody biomass fuels in a 20kWth bubbling fluidised bed combustor. (15th March 2019) - Chi, Hetian; Pans, Miguel A.; Sun, Chenggong; Liu, Hao
Graphical abstract: Highlights: Lime added to biomass as a countermeasure to agglomeration in BFB combustion. Defluidisation time extensively prolonged for biomass fuels with lime addition. Reduced K/Ca ratio in ash leads to smaller agglomerates & less sand cracking. Fe precipitates from sand & reacts with molten ash, accelerating agglomeration. Lime addition to fuels hinders the acceleration caused by Fe precipitation. Abstract: The unique fuel flexibility of fluidised bed system facilitates the combustion of low quality solid fuels such as agricultural residues, but may suffer from serious bed agglomeration problems especially when operating at the high end of the typical fluidised bed combustion temperature range (800–900 °C). In this study, a 1.5 wt% lime addition to biomass fuels was investigated as a countermeasure to agglomeration for the combustion of pelletised wheat straw and miscanthus in a 20 kW bubbling fluidised bed (BFB) combustor using quartz sand as the bed material. Comparing to the widely studied agglomeration countermeasures such as bed additives and alternatives, the lime addition to fuel can provide a continuous on-site agglomeration counter action. Without lime addition, defluidisation as a result of bed agglomeration occurred once the bed temperature reached 860 °C and 877 °C for miscanthus and wheat straw respectively. However, with the lime addition, stable combustion could be achieved at 900 °C for both fuels with a substantially prolonged operation time. The obtained agglomerates were characterised using CAMSIZER, XRD and SEM/EDX and the results showed that the presence of lime in the fuel could significantly reduce the agglomerates size by forming high melting point calcium silicates/phosphates which hinder the K-rich molten substance attachment and result in heterogeneous coating layers in the agglomerates. The results of this study clearly indicate that using lime as fuel additive can realise the combustion of the problematic non-woody biomass fuels by considerably reducing the bed agglomeration propensity in practical fluidised bed combustion plants.